229 Uncomplicated Diverticulitis: A Proposed Diagnostic Algorithm. (4th May 2021) - Kerr, B; Ahmed, O; Byrnes, C
Abstract: Introduction: Covid-19 has changed surgical practice. Infection risk and hospital pressures means appropriate patient ambulation is paramount. Uncomplicated diverticulitis can be managed as an outpatient. Clinical differentiation of uncomplicated and complicated diverticulitis remains challenging. This study aims to develop a diagnostic algorithm to differentiate complicated from uncomplicated disease prior to imaging. Method: A single-centre retrospective review of 177 patients referred as diverticulitis between Sept-Dec 2018, was performed. Data collected included clinical presentation, biochemistry and imaging. Complicated diverticulitis was defined as occlusion, perforation, abscess formation, fistula and/or bleeding. Inferential parametric analysis was performed to ensure predictive value. Results: Of 177 patients referred, 71 received a consultant diagnosis of diverticulitis. 60 were confirmed and differentiated on CT scan. LIF/lower abdominal pain (P < 0.01) and bowel habit change (P < 0.05) was significantly higher in patients with diverticulitis compared to other pathology. In complicated diverticulitis, symptoms occurred < 4days (P < 0.05), fever was present (P < 0.001) and CRP was > 75. Conclusions: Once diverticulitis diagnosis is made based on pain localisation and change in bowel habit, complicated disease can be predicted by symptom duration (< 4 days), presence of fever and a CRP > 75. Plans to assess these findings prospectively in a Surgical Admissions Unit are currently in development.